CNT‐Supported MoxC Catalysts: Effect of Loading and Carburization Parameters. Issue 8 (15th April 2013) - Frank, Benjamin; Friedel, Klaus; Girgsdies, Frank; Huang, Xing; Schlögl, Robert; Trunschke, Annette
Abstract MoxC/CNT catalysts were prepared through carburization of an oxidic molybdenum precursor impregnated on multiwalled carbon nanotubes (CNTs). The effects of different carburization atmospheres, heating rates, and molybdenum loadings were tested. The catalysts were characterized by using CO temperature‐programmed desorption, XRD, N2 physisorption, SEM, and TEM. The catalytic performance in the steam reforming of methanol was used as a sensitive probe to indicate changes in the catalyst surface during the catalytic action. Contrary to the bulk MoxC catalysts, the heating rate during carburization has no effect on the catalysts. Instead, molybdenum loading and carburization atmosphere are the key factors for catalyst structure and performance. The molybdenum‐based activity decreases at loadings >10 wt % at a constant product selectivity. The CO2/CH4 product ratio indicates changes in the catalyst properties at the loadings <20 wt %, at which the activity is constant. Carburization in 20 % CH4/H2 yields 2 nm sized crystallites of cubic α‐MoC. Carburization in pure H2 and He yields hexagonal β‐Mo2C with a larger particle size. Both phases show different catalytic performances in terms of activity and CO2/CH4 selectivity. Thus, a multiparameter toolbox for fine‐tuning of catalyst properties is presented.